Utilization of dual stable isotope markers (δ13C and δ15N) to determine trophic structure in aquatic environment of Malaysian peat swamp forest - Md Joni, Amirul Azuan; Zulkifli, Syaizwan Zahmir; Mohamat-Yusuff, Ferdaus; Hanapiah, Munirah; Mukhtar, Aqilah; Ismail, Ahmad; Nobuyaki Miyazaki, (Elsevier, 2015)
This study was conducted to develop a preliminary food web model of aquatic environment at the North Selangor Peat Swamp Forest (NSPSF) using stable isotope markers (δ13C and δ15N). The samples were collected from two selected points of peat swamp area representing disturbed and undisturbed areas. Samples collected then underwent analytical procedures before being analysed using an Isotope Mass Ratio Spectrometry (IRMS). Results showed that there are differences in trends of the food web between disturbed and undisturbed area. A consumer in the higher trophic level had significantly higher δ13C and δ15N values compared to the lower consumer. Hemibagus nemurus has become the top predator in disturbed areas while Channa lucius becomes the top predator in undisturbed areas. Sampling throughout the year is highly recommended as different species are only available for a certain period of time due to the water input from the rainfall